2021
DOI: 10.7554/elife.64691
|View full text |Cite
|
Sign up to set email alerts
|

Disease-related mutations in PI3Kγ disrupt regulatory C-terminal dynamics and reveal a path to selective inhibitors

Abstract: Class I Phosphoinositide 3-kinases (PI3Ks) are master regulators of cellular functions, with the class IB PI3K catalytic subunit (p110g) playing key roles in immune signalling. p110g is a key factor in inflammatory diseases, and has been identified as a therapeutic target for cancers due to its immunomodulatory role. Using a combined biochemical/biophysical approach, we have revealed insight into regulation of kinase activity, specifically defining how immunodeficiency and oncogenic mutations of R1021 in the C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 102 publications
(108 reference statements)
4
30
0
Order By: Relevance
“…The putative binding epitopes are indicated in the source data. Multiple nanobodies caused decreased exchange in the helical domain of p110g, which has been observed for previous p110g antibody and small molecule binding partners (Gangadhara et al, 2019;Rathinaswamy et al, 2021;Shymanets et al, 2015) due to the propagation of allosteric changes to the helical domain.…”
Section: Hdx-ms Enabled Identification Of Nanobody Binding Epitopessupporting
confidence: 62%
See 2 more Smart Citations
“…The putative binding epitopes are indicated in the source data. Multiple nanobodies caused decreased exchange in the helical domain of p110g, which has been observed for previous p110g antibody and small molecule binding partners (Gangadhara et al, 2019;Rathinaswamy et al, 2021;Shymanets et al, 2015) due to the propagation of allosteric changes to the helical domain.…”
Section: Hdx-ms Enabled Identification Of Nanobody Binding Epitopessupporting
confidence: 62%
“…This allowed us to identify and characterize p110g-binding nanobodies that activate lipid kinase activity, block activation by Ras, and a p101-binding nanobody that disrupts GPCR activation. Nanobodies were identified that stabilized flexible regions/domains, allowing for high-resolution cryo-EM studies (details described in a separate study, Rathinaswamy et al, 2021). Overall, this work provides an HDX-MS-enabled flow path for the rapid characterization of nanobodies for structural and biochemical studies (Figure 1).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The putative binding epitopes are indicated in the source data. Multiple nanobodies caused decreased exchange in the helical domain of p110 γ , which has been observed for previous p110 γ antibody and small molecule binding partners (Gangadhara et al, 2019; Rathinaswamy et al, 2021; Shymanets et al, 2015) due to the propagation of allosteric changes to the helical domain. Of the nanobodies studied by HDX, we were able to identity putative epitopes for the majority (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Whether these mutants function within the tumor or the surrounding immune environment remains to be confirmed. Activating oncogenic mutants in the regulatory motif of the kinase domain of p110γ (R1021C) have been identified ( 62 ), with bi-allelic inactivating mutations involving the same site (R1021P, R982 frameshift) causing primary immunodeficiencies ( 63 ). We found oncogenic mutations clustered at ABD and p101 interfaces in PIK3CG.…”
Section: Discussionmentioning
confidence: 99%